The Web-Based Osteoarthritis Management Resource My Joint Pain Improves Quality of Care: A Quasi-Experimental Study - Umapathy, Hema; Bennell, Kim; Dickson, Chris; Dobson, Fiona; Fransen, Marlene; Jones, Graeme; Hunter, David J (JMIR Publications, 2015)
BackgroundDespite the availability of evidence-based guidelines for conservative treatment of osteoarthritis (OA), management is often confined to the use of analgesics and waiting for eventual total joint replacement. This suggests a gap in knowledge for persons with OA regarding the many different treatments available to them. ObjectiveOur objective was to evaluate outcomes after usage of a Web-based resource called My Joint Pain that contains tailored, evidence-based information and tools aimed to improve self-management of OA on self-management and change in knowledge. MethodsA quasi-experimental design was used to evaluate the My Joint Pain website intervention over a 12-month period. The intervention provided participants with general and user-specific information, monthly assessments with validated instruments, and progress-tracking tools. A nationwide convenience sample of 195 participants with self-assessed hip and/or knee OA completed both baseline and 12-month questionnaires (users: n=104; nonusers: n=91). The primary outcome measure was the Health Evaluation Impact Questionnaire (heiQ) to evaluate 8 different domains (health-directed activity, positive and active engagement in life, emotional distress, self-monitoring and insight, constructive attitudes and approaches, skill and technique acquisition, social integration and support, health service navigation) and the secondary outcome measure was the 17-item Osteoarthritis Quality Indicator (OAQI) questionnaire to evaluate the change in appropriateness of care received by participants. Independent t tests were used to compare changes between groups for the heiQ and chi-square tests to identify changes within and between groups from baseline to 12 months for each OAQI item. ResultsBaseline demographics between groups were similar for gender (152/195, 77.9% female), age (mean 60, SD 9 years) and body mass index (mean 31.1, SD 6.8 kg/m2). With the exception of health service navigation, mean effect sizes from all other heiQ domains showed a positive trend for My Joint Pain users compared to the nonusers, although the differences between groups did not reach statistical significance. Within-group changes also showed improvements among the users of the My Joint Pain website for self-management (absolute change score=15%, P=.03), lifestyle (absolute change score=16%, P=.02), and physical activity (absolute change score=11%, P=.04), with no significant improvements for the nonusers. Following 12 months of exposure to the website, there were significant improvements for users compared to nonusers in self-management (absolute change score 15% vs 2%, P=.001) and weight reduction (absolute change scores 3% vs -6%, P=.03) measured on the OAQI. ConclusionsThe My Joint Pain Web resource does not significantly improve overall heiQ, but does improve other important aspects of quality of care in people with hip and/or knee OA. Further work is required to improve engagement with the website and the quality of information delivered in order to provide a greater impact.